ANALISA PERHITUNGAN RENCANA ANGGARAN BIAYA STRUKTUR DAN PENJADWALAN GEDUNG RUKO 2 LANTAIDENGAN MENGGUNAKAN STANDAR HARGA SATUAN BANGUNAN PERDA KABUPATEN SIKKA TAHUN 2020 - Sebastianus Hendra Vias Iry; Oktavianus Jori; Dedi Imanuel Pau (SIARTEK - Jurnal Teknik Sipil dan Arsitektur, 2023)
Abstract: A shophouse or shophouse is a building that generally has two or more stories, where the bottom floor is usually used for business premises, and the subsequent floors are used as residences. In constructing this shophouse building, there are many factors needed for the smooth construction of the building. One of the factors in question is the availability of funds or budget. The cost budget is a calculation of the amount of costs required.In calculating the planned cost budget (RAB), the 2020 Sikka Regency Regional Government building unit price standard and the 2017 SNI Work Unit Price Analysis are used. – 2018. In preparing the scheduling, the PDM method was used with the help of Microsoft Excel. From the results of the calculation of the budget planning for the existing structure costs, a 2-story shophouse using the standard Sikka district unit price is IDR 4,866,105,714.14 and the time required to complete the structural work (columns, beams and floor plates) has been planned for a duration of 51 day.